2015
DOI: 10.1155/2015/717959
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Inducing Activity of Marine SpongeHaliclonasp. Extracts Collected from Kosrae in Nonsmall Cell Lung Cancer A549 Cells

Abstract: Although various anticancer drugs have been developed for the treatment of nonsmall cell lung cancer, chemotherapeutic efficacy is still limited. Natural products such as phytochemicals have been screened as novel alternative materials, but alternative funds such as marine bioresources remain largely untapped. Of these resources, marine sponges have undergone the most scrutiny for their biological activities, including antiinflammatory, antiviral, and anticancer properties. However, the biological mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Colonies consisting of over 50 cells were counted by FluorChem E (San Jose, CA). Plating efficiency (PE) and survival fraction (SF) from the counted colonies were calculated according to Equations (2) and (3) , respectively 20 :…”
Section: Methodsmentioning
confidence: 99%
“…Colonies consisting of over 50 cells were counted by FluorChem E (San Jose, CA). Plating efficiency (PE) and survival fraction (SF) from the counted colonies were calculated according to Equations (2) and (3) , respectively 20 :…”
Section: Methodsmentioning
confidence: 99%
“…Sponge extract of Haliclona sp. able to increase the percentage of apoptosis and significantly increase the expression of apoptotic gene p53, p21, caspase-8, and caspase-3 in A549 lung cancer cells 13 .…”
Section: Introductionmentioning
confidence: 92%
“…This finding indicated that CA extract decreases the clonogenic property of individual cells of A549, synergistically as a result of cell proliferation assay. Compared to the previous A549 cells' clonogenic assays using a methanol extract of Haliclona sp., this result showed lower colony suppressing ability at a dose of 100 μg/mL, 23 but interestingly, the CA extract showed better performance for this assay at lower concentrations. It might be possible that the A549 cells are more sensitive toward CA extract compared to the extract of Haliclona sp.…”
Section: Discussionmentioning
confidence: 74%